THE YANBU'A AND QIRO'ATI METHODS IN LEARNING THE QUR'AN AT TPQ AISYIYAH JATI KULON KUDUS: METODE YANBU’A DAN QIRO’ATI DALAM PEMBELAJARAN AL-QUR’AN DI TPQ AISYIYAH JATI KULON KUDUS - Intan Devia Maharani; Wasis Wijayanto; Rifananda Septy Anggraeny (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Al-Qur'an Education Park (TPQ) plays an important role in fostering the ability to read the Qur'an, however, TPQ Aisyiyah Kudus still faces several obstacles, namely not having its own building, limited learning facilities, and the uneven reading ability of students. This study aims to understand the history of the establishment of TPQ Aisyiyah Kudus and describe the teaching activities carried out. This study uses a qualitative method with a descriptive approach through observation, interviews, and documentation. The results show that TPQ Aisyiyah applies the Yanbu'a method at the volume level and the Qiro'ati method at the advanced learning. Learning is carried out individually, so that teachers can provide direct guidance to correct students' reading errors. Community support through infaq and religious activities helps maintain the continuity of the learning process. Although facilities and infrastructure are limited, the consistency of learning methods and the role of teachers are able to support the improvement of students' accuracy of makhraj, reading fluency, and tajwid understanding.